Mechanical and dynamic behaviour of walnut shell powder-stabilised clayey soils for sustainable pavement subgrades - Tanyildizi, Muhammed; Zeybek, Abdulhakim (Taylor & Francis Ltd, 2026)
This study examines the effectiveness of walnut shell powder (WNSP), a sustainable, bio-based stabiliser, in enhancing the mechanical and dynamic properties of expansive high-plasticity clay (CH) and low-plasticity clay (CL) soils. Laboratory tests on soils treated with 0-15% WNSP (by dry weight) evaluated its impact on unconfined compressive strength (UCS), California Bearing Ratio (CBR), and resilient modulus ( $ {M_R} $ MR). Optimal improvements were observed at approximately 6% WNSP for CH and 9% for CL soils, with UCS increasing by 33.7% and 41.4%, and CBR by 50.7% and 87.6%, respectively. The resilient modulus, reflecting cyclic stiffness, rose by 149.3% in CH and 31.0% in CL soils. Stress-state-dependent prediction models, particularly Uzan-type formulations, effectively captured the nonlinear resilient behaviour of WNSP-stabilised soils. An extended Modified Uzan model incorporating WNSP-dependent coefficients further improved prediction accuracy. Results highlight WNSP as an eco-friendly, cost-effective stabiliser, utilising agricultural waste for sustainable pavement subgrades.
Keywords: Walnut Shell Powder (Wnsp); Clayey Soil Stabilisation; Resilient Modulus; Stress-Dependent Prediction Models; Sustainable Pavement Subgrades